Maternal history and second trimester uterine artery Doppler in the assessment of risk for development of early and late onset pre-eclampsia and intra uterine growth restriction - Noor, Humera; Manzoor, Mahapara; Sadiq, Saima; Shahzad, Naveed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To evaluate the value of one step uterine artery Doppler and maternal history in the prediction of early onset pre-eclampsia and intra uterine growth restriction in a random population Methods: This study was conducted from 2012 to 2014 Lalla Ded hospital which is a tertiary care hospital associated with GMC Srinagar. This was a prospective study conducted on 200 pregnant women in the second trimester between 19-22 weeks of gestation. Singleton pregnant women were recruited from those attending antenatal care clinics at this hospital over a period of two years. Obstetric and medical history was taken. Transabdominal ultrasound was done and then patients were subjected to Doppler examination of uterine arteries. Results: Mean age of study population was 26.3 years with maximum number of patients in 25-29 year age group. Total numbers of primigravida were 59.5%. Maternal history revealed that 9.5% had previous history of hypertensive pregnancy, 3.5% had history of IUGR. Early onset pre-eclampsia (<32 weeks) was present in 42.9% and late onset pre-eclampsia (>32 weeks) was present in 57.1% cases. Doppler abnormalities were present in 7.5%. In the patients who developed pre-eclampsia 57.1% had uterine artery Doppler abnormalities. Conclusions: Maternal history and uterine artery Doppler at 19-22 weeks gestation is a single step test for the prediction of early onset(<32 weeks) and late onset pre-eclampsia and intra uterine growth restriction.